Evolutionary origins of animal skeletal biomineralization - Murdock, DJE; Donoghue, PCJ (Karger Publishers, 2011)
The evolutionary history of biomineralization in animals is crucial to our understanding of modern mineralized tissues. Traditional methods of unravelling this history have aimed to derive a theory of the development of biomineralization through evolution by the comparison of mineralized systems in model organisms. This has led to the recognition of the ‘biomineralization toolkit’ and raised the question of the homology of mineralized tissues versus convergent or parallel evolution. The ‘new animal phylogeny’ reveals that many of the groups known to biomineralize sit among close relatives that do not, and it favours an interpretation of convergent or parallel evolution for biomineralization in animals. In addition, the fossil record of the earliest mineralized skeletons presents a rapid proliferation of biomineralization across a range of animal phyla with fossil representatives of many modern biomineralizing phyla. A synthesis of molecular, developmental, phylogenetic and fossil evidence demonstrates the convergent or parallel evolution of biomineralization in animals at the phylum level. The fossil record of the Cambrian explosion not only provides vital evidence for the evolution of animal mineralized tissues but also suggests a mechanism for its rapid and synchronous convergent origin.